The Influence of Organizational Support and Proactive Personality on Employee Creativity: The Role of Work Meaning and Devolved Management - Rubiyanta, Rubiyanta; Sunaryo, Sinto (Journal Research of Social Science, Economics, and Management, 2023)
The several factor that have a very large role is Human Resources (HR). The HR element in an organization is considered very important and related to service quality, customer satisfaction and loyalty, competitive advantage, and organizational performance.  This research aims to ensure that the activities of the organization carried out can achieve the goals of the organization or company so that the organization can develop in accordance with its goals. To be able to achieve organizational goals, of course, involves many factors related to each other.  The research method used is quantitative research. The population in this study was 120 employees of CV Ziyad Visi Media. This study used nonprobability sampling with a saturated sampling technique.  The results of this study can find the negative and significant moderation effect of devolved management on the influence of organizational support on employee creativity, meaning that when there is high organizational support, creativity will be high and this can be produced also through low devolved management.  The conclusions of the entire hypothesis proposed in this study are all proven. So there are several implications of theoretical and practical studies in increasing the influence of organizational support and proactive personality on employee creativity: the role of work meaning and devolved management. The implication of studies on theory is that the results of this study can provide a different testing model.